An Empirical Study on the Effect and Quality of Situational English Teaching - Kun Liang (Kassel University Press, 2021)
This paper explores the quality and effect of Situational English Teaching (SET). The subjects are a few non-English majors from five colleges in a Chinese province. Taking college English course for example, a questionnaire survey was carried out to investigate the application state of SET in college English teaching. The survey shows that most college students are poor in English, and the traditional teaching mode cannot effectively improve students’ English level. Hence, it is feasible to apply SET in college English class. Based on the survey results, a new English teaching mode was designed based on SET, and its application effect was investigated empirically. The empirical analysis shows that the SET-based new mode can boost students’ learning interest and comprehensive use of English, and significantly improve the quality of English teaching. The research results enrich the evidence of SET, and promote the application of SET in college English class.